DINAMIKA AKTIVITAS PASAR TANAH KONGSI DI KOTA PADANG 2009-2012 - Sindy Akrefiana; Zulfa; Meri Erawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the dynamics of Pasar Tanah Kongsi in Padang City during 2009–2012, taking the 30 September 2009 earthquake as the starting point and the early recovery phase up to 2012. The research aims to analyze changes in trading activities, the socio-economic conditions of traders, and the role of government policies in post-disaster market rehabilitation. The historical research method was employed, involving heuristics, source criticism, interpretation, and historiography. Data were collected through interviews with traders and market authorities, government archives, documentation, and literature review. The findings reveal that the 2009 earthquake caused significant damage to market infrastructure, resulting in a sharp decline in trading activities and traders’ incomes. Between 2010 and 2012, market activities gradually recovered through traders’ adaptive strategies, such as utilizing temporary trading spaces and adjusting business patterns, supported by local government rehabilitation and reconstruction policies. Pasar Tanah Kongsi remained resilient as a traditional trading center and a space of cross-ethnic social interaction in Padang City.